Pengaruh Efektivitas Dosen Pembimbing Akademik dan Motivasi Belajar Terhadap Prestasi Akademik Mahasiswa Fakultas Komunikasi dan Bisnis Institut Nalanda - Mitta Gautami Pangestu; Hastho Bramantyo; Mujiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning motivation of several students at the Faculty of Communication and Business, Nalanda Institute, particularly those who study while working, which has led to low academic achievement. This condition highlights the need for effective academic advisory roles to assist students in managing their learning process. The purpose of this study is to analyze the influence of the effectiveness of academic advisors and learning motivation on students’ academic achievement. The dependent variable in this study is academic achievement, while the independent variables are the effectiveness of academic advisors and learning motivation. The research employs a quantitative approach with multiple linear regression analysis. Primary data were collected through questionnaires distributed to 120 respondents consisting of undergraduate students from the Buddhist Communication Studies and Buddhist Business and Management programs at the Faculty of Communication and Business, Nalanda Institute. The t-test results indicate that the effectiveness of academic advisors has a significant effect on academic achievement, with a t-value of 5.140 and a significance level of 0.000 (p < 0.05). Learning motivation also has a significant effect, with a t-value of 3.284 and a significance level of 0.001 (p < 0.05). The F-test results show that both variables simultaneously have a significant effect on academic achievement, with an F-value of 22.286 and a significance level of 0.000 (p < 0.05). These findings emphasize that effective academic advising accompanied by high learning motivation can significantly improve students’ academic achievement.